One-sided test for an unknown breakpoint: Theory, computation, and application to monetary theory - Arturo Estrella; Anthony P. Rodrigues (Federal Reserve Bank of New York, 2005)
The econometrics literature contains a variety of two-sided tests for unknown breakpoints in time-series models with one or more parameters. This paper derives an analogous one-sided test that takes into account the direction of the change for a single parameter. In particular, we propose a sup t statistic, which is distributed as a normalized Brownian bridge. The method is illustrated by testing whether the reaction of monetary policy to inflation has increased since 1959.
Keywords: C12; C22; E52; 330; break test; monetary policy reaction function; Zeitreihenanalyse; Statistischer Test; Geldpolitik; Schätzung; USA